The Relationship between Current Account Deficits and Growth in Montenegro: ARDL Bounds Testing Approach - Mustafa Özer; Jovana Žugić; Sonja Tomaš-Miskin (Journal of Central Banking Theory and Practice, 2018)
In this study, we investigate the relationship between current account deficits and growth in Montenegro by applying the bounds testing (ARDL) approach to co-integration for the period from the third quarter of 2011 to the last quarter of 2016. The bounds tests suggest that the variables of interest are bound together in the long run when growth is the dependent variable. The results also confirm a bidirectional long run and short run causal relationship between current account deficits and growth. The short run results mostly indicate a negative relationship between changes in the current account deficit GDP ratio and the GDP growth rate. This means that any increase of the value of independent variable (current account deficit GDP ratio) will result in decrease of the rate of GDP growth and vice versa. The long-run effect of the current account deficit to GDP ratio on GDP growth is positive. The constant (β0) is positive but also the (β1), meaning that with the increase of CAD GDP ratio of 1 measuring unit, the GDP growth rate would grow by 0,5459. This positive and tight correlation could be explained by overlapping structure of the constituents of CAD and the drivers of GDP growth (such as tourism, energy sector, agriculture etc.). The results offer new perspectives and insights for new policy aiming for sustainable economic growth of Montenegro.
Keywords: C22; E17; E27; F32; F41; F43; H62; 330; Current account deficit; ARDL Bounds testing; Granger Causality; Co-integration; Montenegro Economy